The Many Faces of Expanded Dengue Syndrome: A Two-Case Series of Renal and Hepatic–Neurological Organ Involvement in Adult Patients - Putu Nindya Ayu Ningrum Subadra; Anak Agung Ayu Yuli Gayatri; I Ketut Agus Somia; I Made Susila Utama; Ni Made Dewi Dian Sukmawati (Sriwijaya Journal of Internal Medicine, 2026)
Background: The rising global incidence of dengue has been accompanied by increasing recognition of atypical, organ-dominant presentations collectively termed expanded dengue syndrome (EDS), in which severe involvement of the liver, kidney, heart, lung or central nervous system dominates the clinical picture and drives mortality. Objective: To describe two adult men who illustrate contrasting EDS phenotypes — renal and hepatic–neurological organ involvement. Case presentation: Case I, a 30-year-old man with serologically confirmed secondary dengue (IgM-negative, IgG-positive), presented with gross haematuria, dysuria and warning signs and developed acute kidney injury (oliguria, rising creatinine, proteinuria, marked erythrocyturia) on a background of leucopenia, severe thrombocytopenia and haemoconcentration; he recovered fully with carefully titrated crystalloid and renoprotective measures. Case II, a 23-year-old man with primary infection, deteriorated on day six with agitated delirium and acute liver failure (transaminases >100× the upper limit, hyperbilirubinaemia, coagulopathy, hypoalbuminaemia) complicated by hepatic encephalopathy; he improved with supportive care, electrolyte correction and multidisciplinary management. Conclusion: EDS may arise from either secondary or primary infection, and organ dysfunction tends to resolve in step with the natural history of dengue. Meticulous, clinical-group–stratified fluid stewardship and systematic evaluation for intensive-care needs are the cornerstone of management; early recognition of organ-specific complications is essential to reduce preventable morbidity and mortality.